2021
DOI: 10.1158/2159-8290.cd-20-1543
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Durvalumab and Durvalumab plus Tremelimumab Is Associated with Functional STK11 Mutations in Patients with Non–Small Cell Lung Cancer and Is Reversed by STAT3 Knockdown

Abstract: Mutations in the STK11 (LKB1) gene regulate resistance to PD-1/PD-L1 blockade. This study evaluated this association in patients with nonsquamous non-small-cell lung cancer enrolled in three Phase 1/2 trials. STK11 mutations were associated with resistance to the anti-PD-L1 antibody durvalumab (alone/with the anti-CTLA-4 antibody tremelimumab) independently of KRAS mutational status, highlighting STK11 as a potential driver of resistance to checkpoint blockade. Retrospective assessments of tumor tissue, whole … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 44 publications
0
47
0
Order By: Relevance
“…Genetic ablation of STK11 in a KRAS-driven murine model of NSCLC demonstrated an accumulation of neutrophils with T-cell suppressive capacities associated with a decreased number of tumor-infiltrating lymphocytes and a reduced expression of PD-L1 in tumors [74]. In an in vitro model, STK11 extinction did not substantially modify the growth of KRAS-mutant colorectal tumors [75]. Conversely, in an immunocompetent mouse model, tumor growth increased, related to a loss of immune control [75].…”
Section: Tumor-extrinsic Impact Of Stk11/lkb1 Alteration: Interaction...mentioning
confidence: 98%
“…Genetic ablation of STK11 in a KRAS-driven murine model of NSCLC demonstrated an accumulation of neutrophils with T-cell suppressive capacities associated with a decreased number of tumor-infiltrating lymphocytes and a reduced expression of PD-L1 in tumors [74]. In an in vitro model, STK11 extinction did not substantially modify the growth of KRAS-mutant colorectal tumors [75]. Conversely, in an immunocompetent mouse model, tumor growth increased, related to a loss of immune control [75].…”
Section: Tumor-extrinsic Impact Of Stk11/lkb1 Alteration: Interaction...mentioning
confidence: 98%
“…The genes in the PD-L1-H group that were expressed at lower levels exhibited a negative relation with immunotherapy. CCL26, for example, has been shown to be highly expressed in recurrent hepatocellular carcinoma (HCC) ( 33 ), while CXCL2 is highly expressed in STK11-mutated NSCLC, which has a poorer response rate to ICIs ( 34 ). Notably, STK11 mutations were rarer in the PD-L1-H group than the other two groups herein.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IL-6 knockdown in cancer associated fibroblasts (CAF) increased IFN-γ on CD8-postive T cells and IL-6 blockade could reverse anti-PD-L1 resistance in an HCC mouse model [ 48 ]. Recently, a comprehensive study in non-small cell lung cancer demonstrated that reduction in STAT3 in the tumor microenvironment using an antisense oligonucleotide reversed immunotherapy resistance in preclinical STK11 knockout mouse models [ 49 ]. Supporting these data, inhibition of the AURKA/STAT3 signaling pathway promoted effective T-cell infiltration into the tumor microenvironment and improved anti-PD-1 efficacy [ 50 ].…”
Section: Discussionmentioning
confidence: 99%